Love Signs in Sabrina Carpenter's Lyrics Album Short n' Sweet - Putri Raya, Hafshah Santia; Otong Setiawan Djuharie; Erlan Aditya Ardiansyah (Edukasi Lingua Sastra, 2025)
This study aims to describe the representamen, object, and interpretant found in Sabrina Carpenter’s lyrics and how those elements reflect the types of love. This research is classified as descriptive qualitative research. The researcher uses content analysis with an interpretive framework based on Charles Sander Peirce’s semiotics theory. The data for this research consist of the lyrics of three songs from Sabrina Carpenter’s Short n’ Sweet album entitled “Please Please Please”, “Juno”, and “Sharpest tool”. The research result show that there are three types of love in the lyrics of these songs: self love, intimate love, and obsessive love. The love signs in the songs are conveyed through peirce’s triadic theory, which includes representamen,object, and interpretant. The songs in this album are narrated from a first-person point of view, and the narrator also exhibits characteristics of woman’s language, including lexical hedges, intensifiers, emphatic stress, super polite forms, tag questions, empty adjectives, and precise color terms.